Adrenal Insufficiency in Australia: Is it Possible that the Use of Lower Dose, Short-Acting Glucocorticoids has Increased the Risk of Adrenal Crises? - Rushworth, R. L.; Torpy, D. J. (Hormone and Metabolic Research, 2015)
Morbidity from adrenal insufficiency (AI) in Australia is poorly described. The objective of this study was to evaluate AI morbidity patterns in adults between 1999/2000 and 2011/2012 using national databases. A descriptive study of hospitalisations for AI and adrenal crises (AC) in adults and trends in prescriptions for 2 short-acting glucocorticoids (GC) was designed. The setting was the Australian healthcare system. Main outcome measures are the trends in hospitalisation and prescription rates. There were 7 378 hospital admissions for treatment of AI in adults between 1999/00 and 2011/12. Of these, 29.5% were for an AC. Admission rates for AC increased from 9.5 to 12.4 admissions/106/year (p<0.05). There was a 5.8% decrease in admission rates for AI (excluding AC), from 27.0 to 25.5/106/year (p=ns). Short-acting GC [hydrocortisone (HCT) and cortisone acetate (CA)] prescription rates increased significantly (p<0.001) from 3 176.1/106 to 3 463.8/106. Prescription rates for CA decreased by 22.4% (p<0.001) but HCT prescription rates increased to 77.1% (p<0.001). The increase in AC admission rates was positively correlated with the rise in both the total GC prescription rate (r=0.63, p<0.05) and the HCT prescription rate (r=0.74, p<0.01). Over the 13-year study period, there was a 30.8% increase in hospitalisation rates for ACs and a concomitant 77.1% increase in prescribing of HCT. The association between AC events and HCT use and/or reduced effective GC dose is plausibly causal, but confirmatory studies are required before suggesting any change to GC replacement in AI.
Keywords: Addison’s disease; adrenal crisis; glucocorticoid replacement